Introduction to the Apocrypha : Jewish books in Christian bibles - Wills, Lawrence M. (Lawrence Mitchell), 1954- (Yale University Press, 2021)
"Challenging the way Christian and non-Christian readers think about the Apocrypha, this is an ambitious introduction to the deuterocanonical texts of the Christian Old Testaments. Lawrence Wills introduces these texts in their original Jewish environment while addressing the very different roles they had in various Christian canons. Though often relegated to a lesser role, a sort of "Bible-Lite," these texts deserve renewed attention, and this book shows how they hold more interest for both ancient and contemporary communities than previously thought"--